2014
DOI: 10.1021/om500332n
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I) Complexes of the Conformationally Rigid IBioxMe4Ligand: Preparation of Mono-, Bis-, and Tris-ligated NHC Complexes

Abstract: The preparation and characterisation of a series of mono-, bis-and tris-ligated rhodium(I) complexes of Glorius' conformationally rigid bioxazoline derived N-heterocyclic carbene ligand IBioxMe 4 are described. (3) were each isolated by careful choice of the reaction conditions. Further substitution and salt metathesis reactions of 1 -3 were investigated and derivatives containing CO, norbornadiene and cyclopentadienyl ancillary ligands were readily isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 92 publications
3
19
0
Order By: Relevance
“…The development of new motifs as ligand platforms for catalysis with the phenomenally successful N‐heterocyclic carbenes (NHCs) remains an active area of research . In this regard, the fusion of two immensely successful ligands in homogeneous catalysis, that is, oxazolidines and imidazole‐based N‐heterocyclic carbenes, has resulted in an interesting new breed of fused bicyclic N‐heterocyclic ligands derived from a hybrid oxazolidine–imidazole motif . In asymmetric catalysis, owing to their unique restricted rotation along the N–C bond housing the chiral substituent, this type of ligand exhibits promising enantioselectivities over conventional chiral ligands in many reactions such as the Michael addition, benzoin condensation, α‐arylation, Stetter reaction, Coates–Claisen rearrangement, and the hydration of α‐halo aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…The development of new motifs as ligand platforms for catalysis with the phenomenally successful N‐heterocyclic carbenes (NHCs) remains an active area of research . In this regard, the fusion of two immensely successful ligands in homogeneous catalysis, that is, oxazolidines and imidazole‐based N‐heterocyclic carbenes, has resulted in an interesting new breed of fused bicyclic N‐heterocyclic ligands derived from a hybrid oxazolidine–imidazole motif . In asymmetric catalysis, owing to their unique restricted rotation along the N–C bond housing the chiral substituent, this type of ligand exhibits promising enantioselectivities over conventional chiral ligands in many reactions such as the Michael addition, benzoin condensation, α‐arylation, Stetter reaction, Coates–Claisen rearrangement, and the hydration of α‐halo aldehydes .…”
Section: Introductionmentioning
confidence: 99%
“…6 The concept of 'bulky-yet-flexible' NHC ligands has emerged as a rationale for the success of a number of series of bulky ligands in transition metal catalysis. 16, 17 Chaplin has recently explored the co-ordination chemistry of IBiox ligands with rhodium and iridium, [18][19][20][21] and has shown that despite the fact that it holds some steric bulk near the metal centre, C-H activation processes do not occur, unlike with the corresponding I t Bu species. 9 This theory has been put forward to explain the successful use in catalysis of various ligands such as the IBiox series of NHCs, 7,11 IPr* and derivatives, 9,[12][13][14] and IPent 8 and its analogues 15 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…21 The IBiox series has mainly been used by Glorius 7 and Lautens, 21 particularly in palladium and rhodium catalysis, but their use is far from general and has only been examined for a limited number of applications. 22,23 Another class of bulky NHCs is represented by the Cyclic Alkyl Amino Carbenes (CAAC), developed by Bertrand. 15 These carbenes are based on a pyrrolidine ring bearing two quaternary carbon centers, making it one of the most electrondonating types of NHCs.…”
Section: Introductionmentioning
confidence: 99%